What really brings you here today? Applying McWhinney's Taxonomy of Patient Behaviour between the first waves of COVID-19 - Donavan de Souza Lucio; Ana Carolina Liberatti Barros (CSIRO Publishing, 2022)
IntroductionDr Ian McWhinney argued that the behaviour of patients should be classified in parallel with the taxonomy of disease. Therefore, he proposed a Taxonomy of Patient Behaviour, taking the doctor-patient contact as the reference point. AimTo assess McWhinney's Taxonomy of Patient Behaviour and explore its associations with patient age and gender, type, modality and the weekday of the appointment, in the context of the coronavirus disease 2019 (COVID-19) pandemic. MethodsThis was a cross-sectional study in a Community Health Centre in Florianópolis, Brazil. We retrospectively collected data from electronic medical records and analysed 4 consecutive weeks of our clinical encounters where every appointment had the patient's motivation for seeking their medical appointment coded as: 'limit of tolerance', 'limit of anxiety', 'heterothetic', 'administrative', or 'no illness'. ResultsThere were 647 appointments. The frequencies of the taxonomic classifications were: 27.8% 'administrative', 26.6% 'limit of tolerance', 21.8% 'limit of anxiety', 18.1% 'no illness', and 5.7% 'heterothetic'. Female patients had more consultations classified as 'heterothetic' and 'limit of anxiety'. 'Limit of tolerance' and 'heterothetic' were more frequent in face-to-face appointments than in remote (on-line) consultations, and most of the 'limit of anxiety' consultations were same-day appointments. The average patient age was slightly higher on appointments classified as 'heterothetic' and lower on 'limity of anxiety' appointments. DiscussionThe COVID-19 pandemic may have influenced the higher 'administrative' and 'limit of anxiety' frequency presentations. We hope to encourage other family doctors to adopt this system during their consultations and teaching functions and, perhaps, inspire more complex investigations.